1977
DOI: 10.1007/bf01906363
|View full text |Cite
|
Sign up to set email alerts
|

Time course of electron microscopic alterations in the hypertrophied myocardium of Goldblatt rats

Abstract: In Goldblatt rats, electron microscopic investigations of morphological changes in heart tissue during the compensatroy stage of pressure induced cardiac hypertrophy were performed. Myocardial cellular size enlarged considerably within the first 4 weeks after renal artery coarctation. An enlargement of the T-tubular system is particularly striking. The ratio of myofibril volume to total cell volume is significantly increased from the 4th-24th week and can at least partially explain a rise in developed tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…It is also worth noting that the values for total Ca content over the enzymes' activatory range, as opposed to the higher values required for buffering, are much closer to estimates made in situ by using X-ray probe microanalysis (e.g. Somlyo et al, 1985;Wendt-Gallitelli, 1986;LeFurgey et al, 1986). These data are thus in some ways contrary to the conclusion of Nicchitta & Williamson (1984) that the effects of spermine on Ca2+ egress would allow mitochondria to buffer extramitochondrial Ca2' at lower Ca content; however, it is unclear how a process which depends on egress saturation would be affected by a change in Km.…”
Section: Discussionsupporting
confidence: 51%
“…It is also worth noting that the values for total Ca content over the enzymes' activatory range, as opposed to the higher values required for buffering, are much closer to estimates made in situ by using X-ray probe microanalysis (e.g. Somlyo et al, 1985;Wendt-Gallitelli, 1986;LeFurgey et al, 1986). These data are thus in some ways contrary to the conclusion of Nicchitta & Williamson (1984) that the effects of spermine on Ca2+ egress would allow mitochondria to buffer extramitochondrial Ca2' at lower Ca content; however, it is unclear how a process which depends on egress saturation would be affected by a change in Km.…”
Section: Discussionsupporting
confidence: 51%
“…Anversa et al 31 demonstrated in rabbit myocardium with experimental advanced hypertrophy that the TT system was dilated. This phenomenon was then observed in other animal models of hypertrophy 32,33 and heart failure. 34 Later on, dilated TTs were also found in human heart tissues of hypertrophic cardiomyopathy, congestive cardiomyopathy, dilated cardiomyopathy, ischaemic cardiomyopathy, aortic valvular disease, and congenital heart diseases associated with obstruction to right-ventricular outflow.…”
Section: Morphological Changes Of Tts In Hypertrophy and Heart Failurementioning
confidence: 86%
“…Quantitative changes in cellular constitutents are characterized by a decrease in the volume ratio: mitochondridmyofibrils (Lund and Tomanek, 1978;Tomanek et al, 1979;Tomanek, 1979a,b;Tomanek and Hovanec, 1981). A decrease in this ratio due to a relative increase in myofibrillar volume and/or a relative decrease in mitochodrial volume has also been found in other forms of pressure overload, i.e., aortic constriction (Page et al, 1972;Goldstein et al, 1974;Anversa et al, 1976;Lund and Tomanek, 1978) and renal artery constriction (Wiener et al, 1979;Wendt-Gallitelli and Jacob, 1977). Such a decrement in the ratio of energy-producing to energy-consuming organelles could presumably limit myocardial metabolism under conditions requiring high 0 2 utilization.…”
mentioning
confidence: 95%